Human and societal transformations are critical for food system responses to the climate crisis - Challinor, Andrew Juan; Hellin, Jon; Meadu, Vanessa; Spillane, Charles; McKeown, Peter C.; Whitfield, Stephen; Taylor, Steve; Grey, Carmody T.; Veeger, Marieke; Rutting, Lucas (Inter-Research, 2025)
Faced with the growing climate crisis, there are calls for transformative adaptation, a climate response that address the root causes of vulnerability and requires radical change in food systems. Transformation of food systems is, hence, essential to deal with the ongoing climate crisis and to fulfil wider sustainability and development challenges from local to global scales. Transformed food systems must minimise vulnerability to shocks while delivering environmental, social, and economic benefits. This need can only be met by embracing food systems transformation as a process of social and individual change that contributes to transformative adaptation. The scale of this societal and environmental challenge demands an equally grand vision – one that integrates climate, sustainability and systems thinking with human psychology, beliefs and values, and shared understandings. Such a vision, with community and individual transformation at its core, has the potential to deliver multiple benefits to society through transformative food systems change, livelihood resilience and climate change adaptation and mitigation. Fostering conditions that support both individual transformation and the development of collective understandings, therefore, needs to be a core part of any strategies to transform food systems. In this opinion piece we provide a framework to guide this transformative drive towards societal climate resilience.